2013
DOI: 10.1038/jid.2013.70
|View full text |Cite|
|
Sign up to set email alerts
|

Multiple Congenital Melanocytic Nevi and Neurocutaneous Melanosis Are Caused by Postzygotic Mutations in Codon 61 of NRAS

Abstract: Congenital melanocytic nevi (CMN) can be associated with neurological abnormalities and an increased risk of melanoma. Mutations in NRAS, BRAF, and Tp53 have been described in individual CMN samples; however, their role in the pathogenesis of multiple CMN within the same subject and development of associated features has not been clear. We hypothesized that a single postzygotic mutation in NRAS could be responsible for multiple CMN in the same individual, as well as for melanocytic and nonmelanocytic central n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
250
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 286 publications
(268 citation statements)
references
References 49 publications
12
250
2
4
Order By: Relevance
“…Recently, different studies have demonstrated that early embryonic/post zygotic somatic mutations in the NRAS gene are implicated in the development of neurocutaneous melanocytosis, a rare congenital disorder, in which affected patients have an increased number of melanocytes in the leptomeninges and the skin, with a large congenital melanocytic nevus usually associated with so-called "satellites" in the vicinity, and childhood melanoma of the central nervous system [46][47][48]. In line with these observations, recently it has been shown that primary melanoma of the CNS in children carries oncogenic mutations in NRAS, unlike primary melanoma of the central nervous system in adults, in which NRAS is not a common driver oncogene [46].…”
Section: Nras In Melanocytic Cell Neoplasmsmentioning
confidence: 99%
“…Recently, different studies have demonstrated that early embryonic/post zygotic somatic mutations in the NRAS gene are implicated in the development of neurocutaneous melanocytosis, a rare congenital disorder, in which affected patients have an increased number of melanocytes in the leptomeninges and the skin, with a large congenital melanocytic nevus usually associated with so-called "satellites" in the vicinity, and childhood melanoma of the central nervous system [46][47][48]. In line with these observations, recently it has been shown that primary melanoma of the CNS in children carries oncogenic mutations in NRAS, unlike primary melanoma of the central nervous system in adults, in which NRAS is not a common driver oncogene [46].…”
Section: Nras In Melanocytic Cell Neoplasmsmentioning
confidence: 99%
“…This mirrors the spectrum of severity seen in other known mosaic disorders involving oncogenes and tumour suppressor genes, such as congenital melanocytic naevus syndrome and the PIK3CA ‐related overgrowth spectrum (PROS) disorders 5, 6. Suspected cases of ‘mild’ Proteus syndrome have previously been described in the literature, prior to the discovery of the underlying genetic mutation 7, 8, 9, 10.…”
mentioning
confidence: 58%
“…A growing number of cancer predispositions linked to postzygotic mosaicism might cause a comparably high individual risk as established in familial CPS [11]. However, these patients usually present with a recognizable phenotype.…”
Section: Discussionmentioning
confidence: 99%